2018
DOI: 10.1016/j.ypmed.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Adding folic acid to corn Masa flour: Partnering to improve pregnancy outcomes and reduce health disparities

Abstract: Although strides have been made in preventing neural tube defects (NTDs), Hispanic women remain more likely to have a baby born with an NTD and less likely to know the benefits of, or consume, folic acid than women of other race/ethnic groups. In 1998, the U.S. Food and Drug Administration (FDA) mandated that all enriched cereal grain products be fortified with folic acid; however, corn masa flour (CMF), used to make many corn products that are a diet staple of many Hispanic groups, was not included under this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…This may in part be due to lower consumption of cereals and enriched grains, which are required to be fortified with folic acid in the US, and higher consumption of staple foods made with corn flour (masa), which was not fortified during the study period. To address folate insufficiency and neural tube defects (NTDs) in this population, the U.S Food and Drug Administration recently authorized voluntary fortification of corn flour in 2016 [45]. Many other countries do not have any mandatory folate fortification.…”
Section: Discussionmentioning
confidence: 99%
“…This may in part be due to lower consumption of cereals and enriched grains, which are required to be fortified with folic acid in the US, and higher consumption of staple foods made with corn flour (masa), which was not fortified during the study period. To address folate insufficiency and neural tube defects (NTDs) in this population, the U.S Food and Drug Administration recently authorized voluntary fortification of corn flour in 2016 [45]. Many other countries do not have any mandatory folate fortification.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that acculturation, an individual's experience entering a new culture, is a mediating factor for NTD risk among infants of Mexican-American women, the largest subgroup of Hispanics in the U.S. [12]. In 2016, the March of Dimes, in collaboration with corn masa manufacturer GRUMA, successfully petitioned the FDA to allow for the voluntary fortification of corn masa flours with folic acid in order to reduce NTD-affected pregnancies among lesser acculturated Mexican-American women [13].…”
Section: Introductionmentioning
confidence: 99%
“…9 This is estimated to prevent 40 additional cases of NTDs in Hispanic infants every year. 10 As approximately 50% of pregnancies in the United States are unplanned, universal prophylaxis with daily folic acid of 400 µg (0.4 mg) is recommended for general reproductive-age women, in addition to a folate-rich diet. In women contemplating pregnancy, the intake should commence at least one month before conception and continue till 12 weeks gestation for maximal protection.…”
mentioning
confidence: 99%